Comparative studies of hydration behaviour and density of Pyrrolidone K-30, PEG 6000 and PEG 20000 - Sultana, Sakina; Ohidullah, Md; Saifuddin, AHM; Hossain, Md Saddam (Bangladesh Pharmaceutical Journal, 2015)
A comparative study was conducted on aqueous solutions of Pyrrolidone K-30 and Polyethylene glycols of molecular weight 6000 and 20000, respectively for investigating their hydration behaviour in terms of intrinsic viscosity and density. In the study, Pyrrolidone K-30 exhibited the intrinsic viscosity of ~14 g/ml, while PEG 6000 and PEG 20000 revealed the intrinsic viscosities of 18 g/ml and 28 g/ml, respectively at a room temperature of 298 ± 1º K. Thus, among these three compounds PEG 20000 exhibited the highest intrinsic viscosity which was interesting. In density measurement this compound showed a non-linear trend of change in density as concentration was varied. Such results were opposite to that observed with the remaining two compounds. Bangladesh Pharmaceutical Journal 18(1): 48-52, 2015